2014
DOI: 10.1126/scitranslmed.3007974
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of CXCR2-Mediated MDSC Tumor Trafficking Enhances Anti-PD1 Efficacy

Abstract: Suppression of the host's immune system plays a major role in cancer progression. Tumor signaling of programmed death 1 (PD1) on T cells and expansion of myeloid-derived suppressor cells (MDSCs) are major mechanisms of tumor immune escape. We sought to target these pathways in rhabdomyosarcoma (RMS), the most common soft tissue sarcoma of childhood. Murine RMS showed high surface expression of PD-L1, and anti-PD1 prevented tumor growth if initiated early after tumor inoculation; however, delayed anti-PD1 had l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
546
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 631 publications
(568 citation statements)
references
References 47 publications
21
546
1
Order By: Relevance
“…Relieving neutrophil-induced immunosuppression may be one way to improve immunotherapy. Indeed, experimental studies have shown that anti-programmed cell death protein 1 (PD1) or anti-PD1 and anti-cytotoxic T lymphocyte-associated antigen 4 (CTLA4) synergizes with anti-CXCR2 or anti-Ly6G, respectively, to delay tumor growth 197,198 . These studies support the concept that combining cancer immunotherapies with neutrophil suppression may increase therapeutic benefit.…”
Section: Combining Neutrophil Targeting With Other Anti-cancer Therapiesmentioning
confidence: 99%
“…Relieving neutrophil-induced immunosuppression may be one way to improve immunotherapy. Indeed, experimental studies have shown that anti-programmed cell death protein 1 (PD1) or anti-PD1 and anti-cytotoxic T lymphocyte-associated antigen 4 (CTLA4) synergizes with anti-CXCR2 or anti-Ly6G, respectively, to delay tumor growth 197,198 . These studies support the concept that combining cancer immunotherapies with neutrophil suppression may increase therapeutic benefit.…”
Section: Combining Neutrophil Targeting With Other Anti-cancer Therapiesmentioning
confidence: 99%
“…11 Tumor microenvironment constituents may also develop checkpoint blockade resistance as reported previously by others. 8,20,21 Here, we show that repeated intraperitoneal administration of mAbs targeting the PD-1/PD-L1 axis induces fatal hypersensitivity reactions specifically in the orthotopic 4T1 murine mammary carcinoma model which has previously been shown to express PD-L1 in vivo. 22 We observed >85% mortality in tumor bearing mice receiving anti-PD-1 or anti-PD-L1 treatments upon repeated dosing.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, strategies that condition the microenvironment to become more receptive to T cells with anti-tumor activity may enhance tumor eradication. For instance, blockade of CXCR2-mediated MDSC trafficking into transplanted rhabdomyosarcomas increases the efficacy of anti-PD1 therapy [186]. In an orthotopic pancreatic tumor model, the triple combination of gemcitabine, TAM blockade via CSF1R inhibition and anti-CTLA4 or the quadruple combination with anti-PD1 is most effective at inducing tumor regression [35].…”
Section: Immunotherapeutic Strategies To Enhance the Response To Antimentioning
confidence: 99%